Best Answer

4r +3 = 3r-2

r + 3=-2

r=-5

basically

collect terms so that you get one coefficient of r (in this case 4r on one side and 3r on the other. To get the three r over to the other side you subtract 3r on both sides.) Then r+ 3=-2, so that's simple algebraic manipulation.

Q: Solve 4r plus 3 equals 3r- 2 for r?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(3r + 18)/12 = (4r - 48)/4Multiply both sides by 12: (3r + 18) = 3*(4r - 48)or: 3r + 18 = 12r - 144Subtract 3r from both sides: 18 = 9r - 144Add 144 to both sides: 162 = 9rDivide both sides by 9: 18 = rAnswer: r = 18

9y subtract 11 equals 7

4r + 4 = 5r 4r - r = 3r 4r x r = 4r^2 4r/r = 4

-2=4r+s s=-4r-2 or s=-(4r+2)

It is 4r + 12s

Related questions

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13

(3r + 18)/12 = (4r - 48)/4Multiply both sides by 12: (3r + 18) = 3*(4r - 48)or: 3r + 18 = 12r - 144Subtract 3r from both sides: 18 = 9r - 144Add 144 to both sides: 162 = 9rDivide both sides by 9: 18 = rAnswer: r = 18

It is (7 + a)r.

It simplifies to: 2s+4R

9y subtract 11 equals 7

-13

4r + 13 = 57subtract 13 from both sides:4r + 13 - 13 = 57 -134r = 44divide both sides by 4 to solve for r:4r/4 = 44/4r = 11

4r + 4 = 5r 4r - r = 3r 4r x r = 4r^2 4r/r = 4

s = -2 -4r

-2=4r+s s=-4r-2 or s=-(4r+2)

If you mean: 10+4r = 30 then it works out that r = 5

r=8